Study on Road Performance of Cement-Stabilized Recycled Aggregate Base with Fiber and Rubber - Yuanzhao Chen; Zhenxia Li; Jin Wang; Chaohui Wang; Jian Guan; Lei Zhang; Xinqi Wang; Xiaguang Hu; Yajie Zhang; Haijun Chen; Yanwei Li (Advances in Civil Engineering)
The purpose is to enhance the recycling utilization rate of old base material and make the cement-stabilized recycled aggregate (RCA) maintain good toughness and crack resistance; rubber particles and basalt fiber admixtures were added to the recycled aggregate. The effects of two different dosages of admixtures on the mechanical properties of the mixture were analyzed; the durability of cement-stabilized base was evaluated; the influence of basalt fiber and rubber particles on the road performance of cement-stabilized recycled aggregate was studied; and scanning electron microscopy was used to analyze the cement-stabilized recycled aggregate mixed with two kinds of admixture. The results show that the increase of basalt fiber dosage improves the mechanical properties of the mixture. The dry shrinkage strain of the mixture decreases, and the frost resistance coefficient increases, indicating that the increase of rubber particles improves the durability of the mixture. When the rubber particles dosage is 0.5%, the basalt fiber dosage is 0.1%, and the recycled aggregate dosage is 50%, the comprehensive rode performance of the mixture is the best. Rubber particles can effectively improve the frost resistance and dry shrinkage of the mixture through its own deformation and shrinkage without damage and slow down the tensile stress caused by dry shrinkage and the compressive stress caused by frost heave. The easy bonding effect of basalt fiber and its pullout effect in the mixture increase the compressive strength and dry shrinkage resistance of the mixture.